2024
DOI: 10.3389/fimmu.2024.1337241
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammatory biomarkers (SII, NLR, PLR and LMR) linked to non-alcoholic fatty liver disease risk

Ke Liu,
Shiyun Tang,
Chenhao Liu
et al.

Abstract: BackgroundSystemic immune-inflammatory biomarkers including systemic immune inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) have been demonstrated to be associated with the risk and severity of various liver diseases. However, studies on their role and clinical significance in metabolic diseases, especially in nonalcoholic fatty liver disease (NAFLD), are limited and results are inconsistent.Methods10821 adults aged 20 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For instance, Liu et al. revealed a significant positive association observed between ln (SII) and NAFLD risk (OR=1.46, 95% CI: 1.27–1.69, P < 0.001), establishing a linear relationship between ln (SII) and NAFLD in a cohort of 10,821 adults from six cycles of the NHANES ( 30 ). Several large cohort studies have demonstrated that an elevated SII is independently associated with an increased risk of CVD mortality ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Liu et al. revealed a significant positive association observed between ln (SII) and NAFLD risk (OR=1.46, 95% CI: 1.27–1.69, P < 0.001), establishing a linear relationship between ln (SII) and NAFLD in a cohort of 10,821 adults from six cycles of the NHANES ( 30 ). Several large cohort studies have demonstrated that an elevated SII is independently associated with an increased risk of CVD mortality ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a positive correlation between SII and increased risk of NAFLD and CVD mortality. For instance, Liu et al revealed a significant positive association observed between ln (SII) and NAFLD risk (OR=1.46, 95% CI: 1.27-1.69, P <0.001), establishing a linear relationship between ln (SII) and NAFLD in a cohort of 10,821 adults from six cycles of the NHANES (30). Several large cohort studies have demonstrated that an elevated SII is independently associated with an increased risk of CVD mortality (31)(32)(33).…”
Section: B Amentioning
confidence: 99%
“…Previous studies have demonstrated a positive correlation between SII and increased risk of NAFLD and CVD mortality. For instance, Liu et al revealed a significant positive association observed between ln (SII) and NAFLD risk (OR=1.46, 95% CI: 1.27-1.69, P <0.001), establishing a linear relationship between ln (SII) and NAFLD in a cohort of 10,821 adults from six cycles of the NHANES (30). Several large cohort studies have demonstrated that an elevated SII is independently associated with an increased risk of CVD mortality (31)(32)(33).…”
Section: B Amentioning
confidence: 99%